Gender, skills and infrastructure: constraints to private sector development in South Asia - Uckat, HI (2020)
This thesis studies firm development and labour markets in South Asia from three different perspectives – gender, skills and infrastructure. Chapter 1 investigates how female career advancement in the workplace impacts on bargaining in the household. It exploits the design of a promotion programme for women in Bangladesh’s garment industry, a sector where women continue to be underrepresented even in low-level management positions. The results suggest that women’s promotions lead to higher bargaining power at home not just for the promoted women, but also for the female subordinates that they supervise. Chapter 2 – written with Christopher Woodruff – turns to analyse the effects of the same promotion programme on factory outcomes. It reports on the importance of selecting managers based on their initial characteristics as compared to training candidates in the same skills. The evidence suggests that formal diagnostics lead factories to choose candidates with higher initial skills, which are predictive of official promotions and performance. Training results in higher promotion rates but has only marginal effects on performance. Soft skills, such as confidence and leadership, are particularly relevant for the success of the new female managers. Lastly, Chapter 3 documents heterogeneous short-term effects of infrastructure improvements on firms in India. It finds large and significant negative impacts on incumbent manufacturing firms close to improved highways, which are driven by initially less profitable, younger and smaller firms. This appears to provide a snapshot of the process of reallocation of resources towards more successful firms when areas become better connected.